A Philippine Strongman's Legislative and Constitutional Reforms Legacy. Issue 1 (April 2023) - Yusingco, Michael Henry Ll.; Mendoza, Ronald U.; Mendoza, Gabrielle Ann S.; Yap, Jurel
This article examines five years of legislation and constitutional reform under former President Rodrigo R. Duterte. An overview of post-1986 republic acts shows administrations being more successful in legislating social and economic laws than political laws. President Duterte is no exception to this, yet his presidency stands out in both legislative productivity and the passage of long-overdue laws. This success is due in part to high presidential approval, a supermajority coalition in Congress, and a unified Cabinet. These strengthen his influence over Congress, raising expectations that charter change can be fulfiled. His administration's failed attempt at federalism then raises questions on his commitment to the policy in the first place. Despite a populist campaign and institutional means at his disposal, Duterte does not appear any different from his predecessors who prioritised economic laws favoured by the business class over deep political reform with broader implications on governance and development.